Analyzing community sustainability practices in Latin America. Cultural diversity, territories and local knowledge - Lorente-Molina, Belén; Zambrano Rodríguez, Carlos Vladimir (My University, 2018)
The presentation will analyze, from several community experiences in Latin America, how the practices of social and environmental sustainability respond to a cultural diversity scheme that is understandable from particular ethno-cultural logics, as well as from different forms of social relations. The experiences contributed by these community processes challenge the International Social Work, and also demand contextualizing the global agenda of social work, since the solutions to the sustainability problems, both environmental and social, although they have common global concerns, in many cases these situations require working from a knowledge that is located, shared and is meaningful to the community. It is clear that we need to advance in the production of comparative methodologies of community work, but on the other hand, we must ensure that these same methodologies are capable of articulating very specific strategies of action that can effectively support the agency, often limited, of individuals, groups and communities, to face the harmful impacts that globalization is producing in the poorest populations and in the environment in which they live. In this sense, it is necessary to emphasize that the possibility of sustainable actions in the environment from local and community spaces in developing countries is often in conflict with the energy and economic interests of large transnational corporations. If the issue of sustainability is going to be a priority for social work across the world, it is essential to assume the political and economic logic that this entails, since community solutions, even if they are the most appropriate, are often difficult to maintain in the face of pressure that these community spaces experiencie daily.
Keywords: Desarrollo sostenible - América Latina; Enviromental social work; Sustainable development; Territorial inequalities